Rail Transit: Exploration with Emphasis on Networks with Ring Lines. Issue 1 (January 2014) - Saidi, Saeid; Wirasinghe, S.C.; Kattan, Lina
Regression analyses were performed to study the relationship between rail transit network parameters (e.g., length of line, age of the system, network topology) with city parameters (e.g., population, city area, population density). Transit ridership patterns in Europe, Asia, and North America were investigated. Ring transit lines were found to be an important factor in network topology and the improvement of transit network efficiency and reliability. Cities that had ring rail transit services were assessed. Parameters that justified the implementation of a rail transit network in a city, particularly a ring line, were analyzed through the investigation of cities that had implemented such services. Ring lines were seen to be less popular in North America than in Europe and Asia. A highly concentrated central business district surrounded by remote residential neighborhoods would make circumferential travel less appealing than in larger and mixed land-use city centers with several cross-town activity centers. Further regression analyses were conducted to investigate the relevant parameters for the length of a ring rail transit line. Arguably, a ring transit line can improve the connectivity and directness of a transit network and thus improve transit ridership.